One "Click" to controlled bifunctional supported catalysts for the Cu/TEMPO-catalyzed aerobic oxidation of alcohols. Issue 43 (13th April 2016) - Fernandes, Antony E.; Riant, Olivier; Jonas, Alain M.; Jensen, Klavs F.
Abstract : A modular strategy is described for the preparation and molecular engineering of multifunctional surfaces using CuAAC chemistry and is applied to the model Cu/TEMPO-catalyzed aerobic oxidation of benzyl alcohol. Abstract : A simple and reliable methodology is described for the preparation of heterogeneous bifunctional catalysts with a high control over surface composition. The strategy relies on the grafting of a mix of catalytic components from an azide-functionalized silica platform using the CuAAC reaction. The resulting finely engineered supported catalysts are employed in the model Cu/TEMPO-catalyzed aerobic oxidation of benzylic alcohol.